Comparative safety profiles of spironolactone, eplerenone, and finerenone: a pharmacovigilance study based on FAERS data from 2004 to 2024 - Ji, Kaiyun; Huang, Xingjun; Wang, Fang; Zhang, Lei; Zheng, Yifan; Ji, Ligang; Ju, Ying; Zhuang, Xiaodong; Li, Jia (Frontiers in Pharmacology, 2026)
BackgroundSpironolactone, eplerenone, and finerenone are three commonly used mineralocorticoid receptor antagonists (MRAs) with cardioprotective and renoprotective effects. However, comparative real-world safety evaluations remain limited. This study aimed to assess and compare the adverse event (AE) profiles of the three MRAs using data from the U.S. Food and Drug Administration Adverse Event Reporting System (FAERS).MethodWe conducted a retrospective descriptive analysis using FAERS data from Q1 2004 to Q4 2024. Four disproportionality methods were employed to detect AE signals, including Reporting Odds Ratio (ROR), Proportional Reporting Ratio (PRR), Bayesian Confidence Propagation Neural Network (BCPNN), and Multi-item Gamma Poisson Shrinker (MGPS). Key safety concerns, such as hyperkalaemia, renal impairment, sexual side effects, and congenital anomalies related to MRAs, were examined.ResultsA total of 8,625 AE reports were identified for spironolactone, 2,045 for eplerenone, and 1,391 for finerenone. The most commonly affected system organ classes were metabolism and nutrition disorders, renal and urinary disorders, and investigations. Hyperkalaemia (1,333 cases, ROR 93.73) and acute kidney injury (1,110 cases, ROR 13.11) were the most frequently reported AEs for spironolactone, while eplerenone showed notable signals for acute kidney injury (263 cases, ROR 14.58) and hyperkalaemia (154 cases, ROR 47.79). Finerenone exhibited particularly strong signals for decreased glomerular filtration rate (179 cases, ROR 434.80) and hyperkalaemia (152 cases, ROR 116.85). Spironolactone was uniquely associated with rare but severe AEs such as male endometriosis (ROR 13,978.20) and 5-α-reductase deficiency (ROR 1,663.95), suggesting significant hormonal effects. Eplerenone showed signals for decreased jugular venous pressure and drug–disease interactions. Finerenone was associated with renal biomarkers but lacked significant sex hormone–related AEs. In terms of AEs involving potassium imbalance or renal impairment, finerenone presented the strongest signals, followed by eplerenone and spironolactone. However, spironolactone showed the highest incidence of sexual and congenital abnormalities.ConclusionThe three MRAs exhibit distinct AE profiles. Hyperkalaemia and renal impairment are shared concerns, while spironolactone requires special attention to hormonal and developmental side effects. Eplerenone shows fewer androgen-related AEs, and finerenone appears safer in this regard. Further clinical studies are needed to validate these findings and inform safer prescribing practices.